The role of FOXO4/NFAT2 signaling pathway in dysfunction of human coronary endothelial cells and inflammatory infiltration of vasculitis in Kawasaki disease - Huang, Hongbiao; Dong, Jinfeng; Jiang, Jiaqi; Yang, Fang; Zheng, Yiming; Wang, Shuhui; Wang, Nana; Ma, Jin; Hou, Miao; Ding, Yueyue; Meng, Lijun; Zhuo, Wenyu; et al. (Frontiers in Immunology, 2023)
Aims: The Ca+/NFAT (Nuclear factor of activated T cells) signaling pathway activation is implicated in the pathogenesis of Kawasaki disease (KD); however, we lack detailed information regarding the regulatory network involved in the human coronary endothelial cell dysfunction and cardiovascular lesion development. Herein, we aimed to use mouse and endothelial cell models of KD vasculitis in vivo and in vitro to characterize the regulatory network of NFAT pathway in KD. Methods and Results: Among the NFAT gene family, NFAT2 showed the strongest transcriptional activity in peripheral blood mononuclear cells (PBMCs) from patients with KD. Then, NFAT2 overexpression and knockdown experiments in Human coronary artery endothelial cells (HCAECs) indicated that NFAT2 overexpression disrupted endothelial cell homeostasis by regulation of adherens junctions, whereas its knockdown protected HCAECs such dysfunction. Combined analysis using RNA sequencing and transcription factor (TF) binding site analysis in the NFAT2 promoter region predicted regulation by Forkhead box O4 (FOXO4). Western blotting, chromatin immunoprecipitation, and luciferase assays validated that FOXO4 binds to the promoter and transcriptionally represses NFAT2. Moreover, Foxo4 knockout increased the extent of inflamed vascular tissues in a mouse model of KD vasculitis. Functional experiments showed that inhibition NFAT2 relieved Foxo4 knockout exaggerated vasculitis in vivo. Conclusions: Our findings revealed the FOXO4/NFAT2 axis as a vital pathway in the progression of KD that is associated with endothelial cell homeostasis and cardiovascular inflammation development.